2008
DOI: 10.1590/s0101-20612008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil lipídico de quatro espécies de peixes da região pantaneira de Mato Grosso do Sul

Abstract: O pescado é um alimento importante na dieta de inúmeros grupos populacionais, não apenas como fonte de proteínas de alta qualidade nutricional, mas ainda como reserva significativa de ácidos graxos poliinsaturados da série ômega 3 (ω-3), aos quais são atribuídos numerosos benefícios à saúde humana ( BADOLATO et al., 1994;ÇELIK;DILER;KÜÇÜKGÜLMEZ, 2005;VILA NOVA;GODOY;ALDRIGUE, 2005). Os ácidos ω-3 e ω-6 são precursores dos ácidos eicosanóides (prostaglandinas, tromboxanas e leucotrienos) e são essencialmente fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 18 publications
4
22
2
2
Order By: Relevance
“…A comparison of the data in Table 1 with previously published data on the composition of the five fish species used in this study, showed they were similar to those of other freshwater fish species that commonly cultivated in Brazil, such as dourado (Salminus maxillosus), pintado (Pseudoplatystoma coruscans), pacu (Piaractus mesopotamicus) and cachara (Pseudoplatystoma fasciatum) (Caula et al, 2008;Ramos-Filho et al, 2008;Fernandes et al, 2014).…”
Section: Chemical Composition Of the Fish Speciessupporting
confidence: 76%
“…A comparison of the data in Table 1 with previously published data on the composition of the five fish species used in this study, showed they were similar to those of other freshwater fish species that commonly cultivated in Brazil, such as dourado (Salminus maxillosus), pintado (Pseudoplatystoma coruscans), pacu (Piaractus mesopotamicus) and cachara (Pseudoplatystoma fasciatum) (Caula et al, 2008;Ramos-Filho et al, 2008;Fernandes et al, 2014).…”
Section: Chemical Composition Of the Fish Speciessupporting
confidence: 76%
“…In the present study, HH was 4.82 for sesame oil and 14.85 for flaxseed oil, much higher values than those reported for fish from the Brazilian Pantanal, (1.49-1.84) and considered quite high for an animal product (RAMOS FILHO et al, 2008).…”
Section: Nutritional Quality Indexescontrasting
confidence: 74%
“…AI and TI were lower than 1 for both sesame and flaxseed oil due to the cardioprotective effect of their PUFA. Ramos Filho et al (2008) also found AI and TI values below 1.0 for Pantanal fish, except for pacu fish, which had a TI of 1.16. in the present study. Uzun et al (2007) found 45.3% LA and 37.0% oleic acid in sesame oil, but they found no linolenic acid fractions.…”
Section: Nutritional Quality Indexesmentioning
confidence: 80%
“…These authors evaluated the byproducts obtained from tilapia aquaculture and observed only traces of eicosapentaenoic acid (EPA, C20: 5n-3) and docosahexaenoic acid (DHA, C22: 6n-3). Moreover, in the present study, the values observed for DHA were higher than for EPA, which corroborates the values that were exhibited for other species of freshwater fish (Andrade et al, 1995;Ramos Filho et al, 2008).…”
Section: Downloaded By [Gazi University] At 08:34 03 February 2015supporting
confidence: 92%